2022
DOI: 10.30872/jakt.v19i1.10389
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh fintech payment dan literasi keuangan terhadap perilaku manajemen keuangan mahasiswa

Abstract: AbstrakPenelitian ini bertujuan untuk menguji pengaruh fintech payment dan literasi keuangan terhadap perilaku manajemen keuangan mahasiswa. Sampel penelitian ini adalah mahasiswa Fakultas Ekonomi UST. Metode untuk mendapatkan data dalam penelitian ini adalah kuantitatif dengan cara melakukan penyebaran kuisioner kepada mahasiswa yang berjumlah 50 responden. Data di analisis menggunakan Regresi Linier Berganda hasil penelitiannya pada Uji t menunjukan variabel (X1) fintech payment berpengaruh positif terhadap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Maka dengan adanya kemudahan tersebut membuat masyarakat juga bisa beradaptasi dengan cepat dalam menggunakan fintech dan tentunya akan mempengaruhi perilaku keuangan mereka. Pada penelitian terdahulu mengenai financial technology, Mukti et al, (2022) telah melakukan penelitian dan hasilnya menunjukkan bahwa fintech payment memiliki pengaruh positif terhadap perilaku keuangan.…”
Section: Pendahuluanunclassified
“…Maka dengan adanya kemudahan tersebut membuat masyarakat juga bisa beradaptasi dengan cepat dalam menggunakan fintech dan tentunya akan mempengaruhi perilaku keuangan mereka. Pada penelitian terdahulu mengenai financial technology, Mukti et al, (2022) telah melakukan penelitian dan hasilnya menunjukkan bahwa fintech payment memiliki pengaruh positif terhadap perilaku keuangan.…”
Section: Pendahuluanunclassified
“…According to Hidayah & Martani (2019) it shows that locus of control strengthens the relationship between fintech payments and financial management behavior. Based on research conducted by Mukti et al, (2022) fintech payments and financial literacy have a positive effect on financial management behavior, whereas according to research conducted by Selian (2020) fintech has no significant effect on financial management behavior.…”
Section: Introductionmentioning
confidence: 95%
“…This theory and reasoning are consistent with the empirical findings of previous research. Although some previous studies did not focus on digital finance and MSME financial behavior, several studies have shown that fintech payments have a positive effect on financial behavior (Huda & Risman, 2024;Erlangga & Krisnawati, 2020;Mukti et al, 2022), digital finance has a positive effect on transactions (Lahusa, 2023;Putri et al, 2022;Kamela et al, 2022). Therefore, the first hypothesis is as follows: H1: Digital Finance has a positive effect on financial behavior of MSMEs Although the management of MSMEs, especially MSEs, tends to be carried out by the business owners themselves, they are also managers, therefore MSME financial management can be influenced by managerial biases.…”
Section: Introductionmentioning
confidence: 99%